Supply Chain Management and Green Economy on Business Continuity for MSMEs in Buleleng Regency - I Gusti Ayu Purnamawati; Elly Herliyani (Badan Riset dan Inovasi Daerah Provinsi Bali, 2026)
Purpose: This study aims to analyze the influence of understanding supply chain management and the green economy on the business continuity of MSMEs in Buleleng Regency. Research methods: This study employs a quantitative approach with purposive sampling. The sample of 57 business actors was selected. Based on the questionnaire results, Supply Chain Management and the Green Economy do not have a significant effect on MSMEs' Business Continuity in Buleleng Regency. Results and discussion: Micro, small, and medium-sized enterprises (MSMEs) are businesses established by individuals or other legal entities to meet consumer needs. When running a business, they should understand aspects of Supply Chain Management and the Green Economy as indicators of quality entrepreneurial readiness. This condition is driven by MSMEs' continued orientation toward short-term sustainability, limited adoption of formal SCM, and the absence of economic incentives and market pressures that encourage the actual implementation of the green economy. High-quality entrepreneurs gain a competitive advantage by implementing SCM effectively and in an organized manner, while not forgetting environmental stewardship. Implication: This study provides strategic recommendations for MSME actors and stakeholders to improve MSME Business Continuity by strengthening managerial understanding and business sustainability.